Determination of virginiamycin M1 residue in tissues of swine and chicken by ultra-performance liquid chromatography tandem mass spectrometry. (1st June 2018) - Wang, Xiaoyang; Wang, Mi; Zhang, Keyu; Hou, Ting; Zhang, Lifang; Fei, Chenzong; Xue, Feiqun; Hang, Taijun
Highlights: A reliable UPLC–MS/MS method for the determination of virginiamycin M1 in tissues of chicken and swine was developed. Tissue samples were extracted with acetonitrile and defatted by N -hexane. The developed method was accurate, sensitive and precise according to the Chinese Ministry of Agriculture guidelines. Abstract: A reliable UPLC–MS/MS method with high sensitivity was developed and validated for the determination of virginiamycin M1 in muscle, fat, liver, and kidney samples of chicken and swine. Analytes were extracted using acetonitrile and extracts were defatted by N -hexane. Chromatographic separation was performed on a BEH C18 liquid chromatography column. The analytes were then detected using triplequadrupole mass spectrometry in positive electrospray ionization and multiple reaction monitoring mode. Calibration plots were constructed using standard working solutions and showed good linearity. Limits of quantification ranged from 2 to 60 ng mL −1 .